Analisis Perhitungan Target costing Sebagai Penentuan Biaya Produksi pada UMKM Soto Ayam Lamongan di Slipi: Analysis of Target Costing Calculation as a Determination of Production Costs in Soto Ayam Lamongan MSMEs in Slipi - Pera Periska; Septi Olivia Nurbaiti; Salsabilla Fathonah; Ayu Apriliyanti; Firzani Islamiyah Dwi Putri (PT Cakrawarti Empat Proksi, 2026)
Price competition and margin pressure require food-related MSMEs to systematically calculate production costs to maintain profitability. This study aims to analyze the production cost calculations applied by the Soto Ayam Lamongan MSME in Slipi and compare them with calculations based on Target costing. The study employs a descriptive qualitative approach using primary data consisting of observations, in-depth interviews with business owners, and documentation of production cost records during the research period; the research sample consisted of Lamongan Chicken Soup SMEs operating in Slipi; the analysis was conducted through cost of goods sold (COGS) calculations and the application of Target costing steps (setting market selling prices, profit targets, target cost calculations, and value engineering for efficiency). The results show that before the implementation of Target costing, total production costs were Rp34,080,000 per month with a COGS of Rp11,360 per serving; after implementation and value engineering, total costs decreased to Rp29,250,000 per month with a COGS of Rp9,750 per serving; net profit increased from Rp4,920,000 to Rp9,750,000 (the 25% profit target was achieved). Research implications: Target costing is effective in helping MSMEs control costs, plan prices, and improve profitability, and is suitable as material for cost accounting training for MSME operators.